712. Identification of a Novel Tedizolid Resistance Mutation in rpoB of Methicillin-Resistant Staphylococcus aureus. (26th November 2018) - Werth, Brian; Penewit, Kelsi; Salipante, Stephen; Shen, Tianwei; Xu, Libin; Nath, Abhinav
Abstract: Background: Tedizolid (TDZ) is an oxazolidinone antimicrobial with broad-spectrum activity against Gram-positive bacteria including methicillin-resistant S. aureus (MRSA). Resistance to TDZ is uncommon but mutations in the 23S rRNA target as well as in the transferable rRNA methyltransferase gene cfr, which also mediate resistance to linezolid and chloramphenicol have been implicated. The objective of this study was to determine whether other TDZ resistance pathways exist in MRSA. Methods: Using a well-characterized MRSA strain, N315, we selected for TDZ resistance by serial passage in escalating concentrations of TDZ in Mueller Hinton broth (MHB) starting with 0.5× the MIC. Once visible growth was achieved a sample of the broth was diluted 1:1, 000 into fresh MHB with twice the previous concentration of TDZ until an isolate with an MIC of ≥4 mg/mL was recovered. This MIC was selected since it is 1 dilution above the breakpoint for resistance ≥2 mg/L). This isolate was subjected to whole genome sequencing (WGS) and MICs to other antimicrobials were assessed. Homology modeling was performed to evaluate the potential impact of the mutation on target protein function. Results: After 10 days of serial passage we recovered a stable mutant with a TDZ MIC of 4 mg/L. WGS revealed a single nucleotide variant (A1345G) in the rpoB gene corresponding to an amino acid substitution at D449N. The following table and figure summarize the changes in drug susceptibility between the parent and evolved strain and reveals the location of the amino acid substitution relative to the TDZ binding site. Conclusion: We have identified a novel mutation in the RNA polymerase gene, rpoB, that mediates oxazolidinone and chloramphenicol resistance. This variant lies outside of the rifampin resistance determinant clusters of rpoB that span from 1, 384 to 1, 464 and 1, 543 to 1, 590, and as expected did not affect rifampin susceptibility. The underlying molecular mechanism by which this single nucleotide variant confers TDZ resistance remains unclear but may involve transcriptional modulation by altered sigma factor binding. Disclosures: All authors: No reported disclosures.